2021
DOI: 10.3389/fevo.2021.618709
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow in Phaseolus Beans and Its Role as a Plausible Driver of Ecological Fitness and Expansion of Cultigens

Abstract: The genus Phaseolus, native to the Americas, is composed of more than eighty wild species, five of which were domesticated in pre-Columbian times. Since the beginning of domestication events in this genus, ample opportunities for gene flow with wild relatives have existed. The present work reviews the extent of gene flow in the genus Phaseolus in primary and secondary areas of domestication with the aim of illustrating how this evolutionary force may have conditioned ecological fitness and the widespread adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 165 publications
(161 reference statements)
0
21
0
Order By: Relevance
“…Selection in common bean has occurred in many regional breeding programs with disparate goals, which commonly develop specific subraces or market classes (Vandermark et al, 2014); this may have enhanced regional adaptation in common bean. Additionally, recent work suggests that continued introgression has helped maintain genetic diversity in common bean, especially between genepool introgression, which may be helpful in maintaining genetic variance and continued yield gains (Chacón-Sánchez et al, 2021;Lobaton et al, 2018). Yet at the same time, several of these bean programs also employ shuttle breeding, which commonly leads to the development of more broadly adapted germplasm (Ortiz et al, 2007).…”
Section: Home Field Advantage Across Species: Comparing Apples and Or...mentioning
confidence: 99%
“…Selection in common bean has occurred in many regional breeding programs with disparate goals, which commonly develop specific subraces or market classes (Vandermark et al, 2014); this may have enhanced regional adaptation in common bean. Additionally, recent work suggests that continued introgression has helped maintain genetic diversity in common bean, especially between genepool introgression, which may be helpful in maintaining genetic variance and continued yield gains (Chacón-Sánchez et al, 2021;Lobaton et al, 2018). Yet at the same time, several of these bean programs also employ shuttle breeding, which commonly leads to the development of more broadly adapted germplasm (Ortiz et al, 2007).…”
Section: Home Field Advantage Across Species: Comparing Apples and Or...mentioning
confidence: 99%
“…Several other studies have shown that gene flow leads to changes in different plant traits. For example, Chacón-Sánchez et al, (2021) reviewed the effects of gene flow between cultivated and wild types of several species of the genus Phaseolus (Leguminosae). Morphological, seed and other traits resulted to be influenced by gene flow events and with important consequences for the species performance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent progress in the development of high-throughput sequencing technologies has allowed the genome assembly of a large number of non-model species and significantly increased genomic information in important crops (Marks et al 2021). Recently, Chacón-Sánchez et al (2021) summarized the genomic resources generated in recent years within the Phaseolus genus, showing their importance to evaluate gene flow between gene pools and even between species. Chromosome-level genome assemblies are available for common bean (Schmutz et al, 2014), tepary bean (Phaseolus acutifolius A.…”
Section: Introductionmentioning
confidence: 99%